2021
DOI: 10.3389/fpls.2021.754325
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Real-Time and Illumina Sequencing to Analyze Transcriptional Regulation of Flavonoid Synthesis in Blueberry

Abstract: Blueberries (Vaccinium corymbosum) contain large amounts of flavonoids, which play important roles in the plant’s ability to resist stress and can also have beneficial effects on human health when the fruits are eaten. However, the molecular mechanisms that regulate flavonoid synthesis in blueberries are still unclear. In this study, we combined two different transcriptome sequencing platforms, single-molecule real-time (SMRT) and Illumina sequencing, to elucidate the flavonoid synthetic pathways in blueberrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
(94 reference statements)
2
10
0
Order By: Relevance
“…The LAR gene, which plays a positive role in proanthocyanin accumulation, had a high expression level at the early stages. Still, its expression was not detected in the ripening stage, which is consistent with previous studies ( Zifkin et al., 2011 ; Colle et al., 2019 ; Tang et al., 2021 ). When the expressions of FLS and LAR were inhibited during fruit ripening, the flavonol and proanthocyanidin syntheses were prevented, while anthocyanin biosynthesis was indirectly promoted.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The LAR gene, which plays a positive role in proanthocyanin accumulation, had a high expression level at the early stages. Still, its expression was not detected in the ripening stage, which is consistent with previous studies ( Zifkin et al., 2011 ; Colle et al., 2019 ; Tang et al., 2021 ). When the expressions of FLS and LAR were inhibited during fruit ripening, the flavonol and proanthocyanidin syntheses were prevented, while anthocyanin biosynthesis was indirectly promoted.…”
Section: Discussionsupporting
confidence: 92%
“…We discovered that the accumulation of flavonols was strongly correlated with the flavonol synthase gene FLS and its cis -regulatory lncRNA. Another study ( Tang et al., 2021 ) also found that when blueberries ripened, their flavonol synthesis and FLS expression both dropped. The LAR gene, which plays a positive role in proanthocyanin accumulation, had a high expression level at the early stages.…”
Section: Discussionmentioning
confidence: 92%
“…Blueberry transcriptome data obtained from Illumina and SMRT sequencing were used to identify the gene family members of SnRK2 in blueberry (Tang et al, 2021). The excavated VcSnRK2 protein sequences were analyzed using the Basic Local Alignment Search Tool (BLAST) program (http://www.ncbi.nlm.nih.gov/ BLAST/) in the National Center for Biotechnology Information (NCBI) database.…”
Section: Gene Isolation and Nomenclaturementioning
confidence: 99%
“…Blueberry fruit injection assays were performed with reference to previous studies (An et al, 2019;Tang et al, 2021). The open reading frame of the SnRK2.3 gene was cloned into the pGreenII62-SK vector to obtain the VcSnRK2.3-pGreenII62-SK vector.…”
Section: Blueberry Injection Assaysmentioning
confidence: 99%
See 1 more Smart Citation